Successful treatment of dupilumab in Kimura disease independent of IgE: A case report with literature review - Yang, Boyun; Yu, Hanxiao; Jia, Minyue; Yao, Wo; Diao, Ran; Li, Bohui; Wang, Yongfang; Li, Ting; Ge, Liuya; Wang, Huiying (Frontiers in Immunology, 2022)
Kimura disease (KD) is a rare and benign chronic inflammatory disease of unknown cause. It is characterized by subcutaneous granuloma of soft tissues in the head and neck region, increased eosinophil count, and elevated serum IgE. Currently, no definitive treatments are recommended. A 57-year-old Chinese man was diagnosed with KD after 7 years of slow subcutaneous masses growth. The patient underwent treatment of oral glucocorticoids for 1 year, but the masses recurred as the dosage was tapered down. Subsequent anti-IgE therapy of omalizumab administered subcutaneously at 450 mg/day at a 4-week interval did not show improvement. The size of masses and serum IgE and circulating eosinophils did not decrease significantly after 19 cycles of continuous treatment. Ultimately, switched strategy of dupilumab was applied at an initial dose of 600 mg, followed by 300 mg every 2 weeks for 4 months. This treatment demonstrated dramatical effects with reduced masses in each area and fast dropdown of eosinophil counts, while the high level of serum IgE remained without changes. Recently, different biologics including anti-IgE, anti-IL-5, and anti-IL-4/IL-13 have been applied to treat KD with satisfied results and help to explore the pathogenesis of this rare disease. To our knowledge, this is the first report that demonstrates the effects of two different biologics in the same patient and reveals the impressive clinical efficacy of dupilumab to treat KD independent of IgE. Therefore, further investigation of the underlying mechanism and the development of diagnosis and treatment of KD is valuable.